Penyerangan Terhadap Petinggi Hamas Di Wilayah Negara Lain Dan Implikasi Hukumnya - Soumena, Ajwar; Wattimena, Josina Augustina Yvonne; Tahamata, Lucia Charlota Octovina (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2024)
Introduction: International law as a law that crosses national borders regulates all forms of rules and principles of international relations law. International law also defines all forms of legal responsibility of countries in acting and their actions towards individuals within national borders whose domains include various issues of concern to the international world such as human rights, international crimes, citizenship issues and so on. International law also carries out global missions such as environmental improvement and sustainable development, international waters, outer space, and so on.Purposes of the Research: Methods of the Research: This research is a normative legal research. The type of research is descriptive analytical. The sources of legal materials used in this study are primary legal materials and secondary legal materials. Supporting data and information are then identified and then systematized for interpretation and arguments are given to obtain conclusions on the problem.Results / Findings / Novelty of the Research: The attack on Hamas leaders in the territory of another country is a violation of state sovereignty in international law. The murder of Ismail Haniyeh was carried out with a guided missile targeting his private residence in Tehran, Iran. The murder took place outside the conflict area and certainly violated the jurisdiction of another country. Sovereignty is a fundamental right for every country in the world as a necessity for the implementation of a legal system in a region in order to provide guarantees for the survival of the population in that region. As one of the subjects of international law, international recognition of a country is based on whether or not the requirements for the formation of a country are met, including according to the 1933 Montevideo Convention, there are four elements of state formation, namely, permanent population, territory, government and the ability to conduct relations with other countries